Unprecedented Catalytic Wet Oxidation of Glucose to Succinic Acid Induced by the Addition of n‐Butylamine to a RuIII Catalyst. Issue 17 (11th August 2016) - Podolean, Iunia; Rizescu, Cristina; Bala, Camelia; Rotariu, Lucian; Parvulescu, Vasile I.; Coman, Simona M.; Garcia, Hermenegildo
Abstract: A new pathway for the catalytic wet oxidation (CWO) of glucose is described. Employing a cationic Ru@MNP catalyst, succinic acid is obtained in unprecedently high yield (87.5 %) for a >99.9 % conversion of glucose, most probably through a free radical mechanism combined with catalytic didehydroxylation of vicinal diols and hydrogenation of the resulted unsaturated intermediate. Abstract : SA with Ru+BuNH2 : Glucose is converted in 87.5 % selectivity to succinic acid at complete conversion under catalytic wet oxidation conditions using Ru III supported on aminopropyl‐functionalized silica‐coated magnetic nanoparticles as the catalyst and n ‐butylamine as the base. The addition of n ‐butylamine provides access to unprecedented high selectivities to succinic acid for a total conversion of glucose by changing the oxidation potential of the Ru species.